The involvement of cancer patients in the four stages of decision-making preceding continuous sedation until death: A qualitative study. (July 2018) - Robijn, Lenzo; Seymour, Jane; Deliens, Luc; Korfage, Ida; Brown, Jayne; Pype, Peter; Van Der Heide, Agnes; Chambaere, Kenneth; Rietjens, Judith
Background: Involving patients in decision-making is considered to be particularly appropriate towards the end of life. Professional guidelines emphasize that the decision to initiate continuous sedation should be made in accordance with the wishes of the dying person and be preceded by their consent. Aim: To describe the decision-making process preceding continuous sedation until death with particular attention to the involvement of the person who is dying. Design: Qualitative case studies using interviews. Setting/participants: Interviews with 26 physicians, 30 nurses and 24 relatives caring for 24 patients with cancer who received continuous sedation until death in Belgium, the United Kingdom and the Netherlands. Results: We distinguished four stages of decision-making: initiation, information exchange, deliberation and the decision to start continuous sedation until death. There was wide variation in the role the patient had in the decision-making process. At one end of the spectrum (mostly in the United Kingdom), the physician discussed the possible use of sedation with the patient, but took the decision themselves. At the other end (mostly in Belgium and the Netherlands), the patient initiated the conversation and the physician's role was largely limited to evaluating if and when the medical criteria were met. Conclusion: Decision-making about continuous sedation until death goes through four stages and the involvement of the patient in the decision-making varies. Acknowledging the potential sensitivity of raising the issue of end-of-life sedation, we recommend building into clinical practice regular opportunities to discuss the goals and preferences of the person who is dying for their future medical treatment and care.